An implementation analysis of a quality improvement project to reduce cesarean section in Brazilian private hospitals - Jacqueline Alves Torres; Tatiana Henriques Leite; Thaís Cristina Oliveira Fonseca; Rosa Maria Soares Madeira Domingues; Ana Claudia Figueiró; Ana Paula Esteves Pereira; Mariza Miranda Theme-Filha; Bárbara Vasques da Silva Ayres; Oliver Scott; Rita de Cássia Sanchez; Paulo Borem; Maria Carolina de Maio Osti; et al. (BMC, 2024)
Abstract Background Brazil has one of the highest prevalence of cesarean sections in the world. The private health system is responsible for carrying out most of these surgical procedures. A quality improvement project called Adequate Childbirth Project ("Projeto Parto Adequado"- PPA) was developed to identify models of care for labor and childbirth, which place value on vaginal birth and reduce the frequency of cesarean sections without a clinical indication. This research aims to evaluate the implementation of PPA in private hospitals in Brazil. Method Evaluative hospital-based survey, carried out in 2017, in 12 private hospitals, including 4,322 women. We used a Bayesian network strategy to develop a theoretical model for implementation analysis. We estimated and compared the degree of implementation of two major driving components of PPA-"Participation of women" and "Reorganization of care" - among the 12 hospitals and according to type of hospital (belonging to a health insurance company or not). To assess whether the degree of implementation was correlated with the rate of vaginal birth data we used the Bayesian Network and compared the difference between the group "Exposed to the PPA model of care" and the group "Standard of care model". Results PPA had a low degree of implementation in both components "Reorganization of Care" (0.17 - 0.32) and "Participation of Women" (0.21 - 0.34). The combined implementation score was 0.39-0.64 and was higher in hospitals that belonged to a health insurance company. The vaginal birth rate was higher in hospitals with a higher degree of implementation of PPA. Conclusion The degree of implementation of PPA was low, which reflects the difficulties in changing childbirth care practices. Nevertheless, PPA increased vaginal birth rates in private hospitals with higher implementation scores. PPA is an ongoing quality improvement project and these results demonstrate the need for changes in the involvement of women and the care offered by the provider.